Effects of germination conditions on 5’-phosphodiesterase activity of selected seeds - Pui, Liew Phing; Mohammed, Abdulkarim Sabo; Mohd Ghazali, Hasanah (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2012)
5'-Phosphodiesterase (5'-PDE) is an enzyme that hydrolyses RNA to form 5'-inosine monophosphate (5'-IMP) and 5'-guanosine monophosphate (5'-GMP), which function as flavour enhancers. Selection of the best producer of 5'-PDE was made by determining the activity of the enzyme in six seeds that have been germinated, namely mung bean (Vigna radiate), soybean (Glycine max), adzuki/red bean (Vigna angularis L.), chick pea (Cicer arietinum), black eye pea (Vigna unguiculata) and petai (Parkia speciosa). Seeds that were not germinated acted as the control. In order to ensure there is no contamination from potential 5'-PDE-producing microorganisms during germination, microbial growth was reduced by using different surface sterilizing treatments where the seeds were soaked in 100 mL solution containing different concentrations of sodium hypochlorite (with or without 0.05% sodium azide) for 5 minutes before rinsing it five times with sterilized distilled water (total 500 mL).The seeds were observed every day for 3 days and the best surface sterilizing treatment was selected based on absence of mold growth and the effects on hypocotyl length. Sodium hypochlorite at 0.3% (v/v) concentration was able to inhibit mold growth in adzuki bean, soybean and chickpea. On the other hand, only 0.1% (v/v) sodium hypochlorite was needed to inhibit mold growth in black eye pea and petai, while mung bean required 0.05% (v/v) sodium hypochlorite to inhibit mold growth. Under these conditions, the growth of hypocotyl (hypocotyls length) was only slightly affected compared to the control. 5'-PDE was extracted from seeds that have been germinated for 24 hours and their control (ungerminated seeds) by homogenization in a blender with 400 mL of 50 mM acetate buffer, pH 4.5. After that, the homogenates were stirred for 30 min and the centrifuged at 9000 rpm for 15 min at 10°C. 5'-PDE activity was determined using thymidine 5'-monophosphate p-nitrophenyl ester as substrate at pH 7.0 and 55°C. The formation of nucleotide monophosphates, the products of reaction, was determined at 405 nm. As a strong presence of phosphomonoesterase (PME) will reduce the yield of nucleotide monophosphates as the enzyme hydrolyzes these products into nucleosides and orthophosphate, PME activity was also determined using p-nitrophenyl phosphate as the substrate at 60°C and pH 5.0. Thus, the seed with the highest 5'-PDE activity and a low PME activity can be selected. Germinated adzuki bean was found to have the highest 5'-PDE activity (0.59 μmol p-nitrophenol/min/mg protein) among the germinated seeds. A time-course study indicated that the level of 5'-PDE in adzuki bean increased with time of germination until 15 hours (0.69 μmol p-nitrophenol/min/mg protein), after which the acitivity decreased until it reached the basal level (0.44 μmol p-nitrophenol/min/mg protein) at 72 hours. On the other hand, PME in the bean was the highest at 9 h germination(0.98 μmol p-nitrophenol/min/mg protein). In general, controls have very low basal level of 5'-PDE activity (0.18-0.42 μmol p-nitrophenol/min/mg protein).